RBaaS: A Robust Blockchain as a Service Paradigm in Cloud-Edge Collaborative Environment - Zhengong Cai; Guozheng Yang; Shaoyong Xu; Cheng Zang; Jiajun Chen; Pingping Hang; Bowei Yang (IEEE Access, 2022)
As a decentralized distributed ledger, blockchain is endowed with immutability, traceability, anonymity, and transparency, which has got rapid development in cryptocurrency and production as a new trend. In the meantime, the occurrence of Blockchain-as-a-Service (BaaS) helps in mitigation of the complexity and difficulty in deployment and management of blockchain systems and makes it easier to concentrate on business logic implementation for developers. However, most existing BaaS systems are hosted in the environment of cloud vendors, which has also incurred vendor lock-in risk and impairs the inherent trustless characteristic of blockchain. Though present BaaS systems own a level of availability by using cloud computing or edge computing as infrastructure, the availability is limited, considering the availability of network connections and the data center itself. In this article, a novel cloud-edge collaborative BaaS paradigm is proposed. With the assistance of redundant blockchain node candidates, leader election, and edge network self-healing components, the proposed BaaS system is equipped to extend BaaS to the on-premises edge or private cloud, and realize high availability of blockchain systems in edge-autonomy and cross-data-center scenarios. Through testing a simplified system in a simulated environment in cloud servers, this proposed BaaS system has an acceptable throughput under specific transaction sending rates without much performance degradation due to containerization and data synchronization compared with the original blockchain on-premises deployment method.